Patients’ Expectations Regarding Medical Treatment: A Critical Review of Concepts and Their Assessment - Laferton, Johannes A. C.; Kube, Tobias; Salzmann, Stefan; Auer, Charlotte J.; Shedden-Mora, Meike C. (Frontiers in Psychology, 2017)
Patients’ expectations in the context of medical treatment represent a growing area of research, with accumulating evidence suggesting their influence on health outcomes across a variety of medical conditions. However, the aggregation of evidence is complicated due to an inconsistent and disintegrated application of expectation constructs and the heterogeneity of assessment strategies. Therefore, based on current expectation concepts, this critical review provides an integrated model of patients’ expectations in medical treatment. Moreover, we review existing assessment tools in the context of the integrative model of expectations and provide recommendations for improving future assessment. The integrative model includes expectations regarding treatment and patients’ treatment-related behavior. Treatment- and behavior outcome expectations can relate to aspects regarding benefits and side effects and can refer to internal (e.g., symptoms) and external outcomes (e.g. reactions of others). Furthermore, timeline, structural and process expectations are important aspects with respect to medical treatment. Additionally, generalized expectations such as generalized self-efficacy or optimism have to be considered. Several instruments assessing different aspects of expectations in medical treatment can be found in the literature. However, many were developed without conceptual standardization and psychometric evaluation. Moreover, they merely assess single aspects of expectations, thus impeding the integration of evidence regarding the differential aspects of expectations. As many instruments assess treatment-specific expectations, they are not comparable between different conditions. To generate a more comprehensive understanding of expectation effects in medical treatments, we recommend that future research should apply standardized, psychometrically evaluated measures, assessing multidimensional aspects of patients’ expectations that are applicable across various medical treatments. In the future, more research is needed on the interrelation of different expectation concepts as well as on factors influencing patients’ expectations of illness and treatment. Considering the importance of patients’ expectations for health outcomes across many medical conditions, an integrated understanding and assessment of such expectations might facilitate interventions aiming to optimize patients’ expectations in order to improve health outcomes.